1990
DOI: 10.1038/bjc.1990.300
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral induction of tumour necrosis factor by systemic administration of Bordetella pertussis vaccine

Abstract: Summary Intratumoral induction of tumour necrosis factor (TNF) by administration of Bordetella pertussis vaccine (BPV) as compared with that by the agent OK-432 was investigated in mice. Two hours after such administration tumour tissues tested were resected from the mice, homogenised, and the TNF activities in the homogenate were assayed using a L-929 fibroblast assay. Intravenous injection of BPV into mice bearing the MM46 carcinoma resulted in a greater concentration of TNF in the tumour homogenate than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We previously reported that systemic administration of the killed vaccine of a Gram-negative bacterium, Bordetella pertussis Tohama strain, causes significant growth inhibition of tumours and induces no symptoms of toxicity in tumourbearing mice (Minagawa et al, 1988(Minagawa et al, , 1990. This encouraged us to attempt to find a less toxic LPS from this vaccine.…”
mentioning
confidence: 99%
“…We previously reported that systemic administration of the killed vaccine of a Gram-negative bacterium, Bordetella pertussis Tohama strain, causes significant growth inhibition of tumours and induces no symptoms of toxicity in tumourbearing mice (Minagawa et al, 1988(Minagawa et al, , 1990. This encouraged us to attempt to find a less toxic LPS from this vaccine.…”
mentioning
confidence: 99%